PROFIL HASIL BELAJAR EKSPERIMEN RANGKAIAN RESISTOR MAHASISWA POLITEKNIK - I Gede Rasagama (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The study aim is to determine the profile of learning outcomes of resistor circuits experiment (RCE), before and after reconditioning learning facilities (job-sheet). Component of learning outcomes of type I includes the ability to accomplish a task preliminary, observational data and calculations, questions answer, sources of error, conclusions, and a bibliography, before and after reconditioning job-sheet. Component of learning outcomes of type II includes increased understanding of resistor circuits concepts (N-Gain) and their retention. The concept includes the experiment goals, KCL, KVL, Ohm's Law, and the nature of circuits. The subjects were students of Class I Prodi Energy Conservation D-IV POLBAN. The research activities carried out consist of in five phases: preparation, data collecting, data processing and analysing, discussion and formulation of conclusions. The research result shows RCE before reconditioning job-sheets that gave the highest learning outcomes type I on observational data and calculations, followed by preliminary tasks, questions answer, a bibliography, conclusions, and the lowest was the source of error. After reconditioning job-sheet, the highest of learning outcomes type I happened at observational data and calculations, followed by preliminary tasks, question answers, sources of error, a bibliography, and the lowest is the conclusion. The overall learning outcomes of type I, after reconditioning job-sheet, is better than before reconditioning job-sheet, with N-Gain is 12%. N-Gain of learning outcomes of type II before reconditioning job-sheet, is the highest on Ohm's Law, the nature of circuit, KVL, KCL, and the lowest is on experimental purposes. N-Gain of learning outcomes of type II after reconditioning job-sheet, is the highest on the nature of circuit, the experiment purpose, Ohm's Law, KCL and the lowest is on the KVL. The overall N-Gain of learning outcomes of type II, before reconditioning job-sheet of 27% and after reconditioning job-sheet of 25%. Retention of learning outcomes of type I has the same pattern as type II, both before and after reconditioning job-sheet, which is likely to increase. Keywords: Profile of learning outcomes, resistor circuits experiment, polytechnic students.